A Multi-Campus Pilot Feasibility Evaluation of a Bystander-Based Sexual Violence Prevention Program: Exploring the Influence of Drinking Behaviors on Bystander Behavior - Williams, Joah L. (Journal of interpersonal violence, 2021)
Researchers and policy makers are devoting considerable attention to the development and evaluation of sexual violence prevention programming for college campuses. Although several programs have been developed over the last decade, questions remain about whether programs can be effectively implemented across diverse campuses and whether individual-level factors like alcohol use moderate program effectiveness. The purpose of this pilot study was to evaluate the impact of a brief, sexual violence prevention program—The Men’s Program—on two diverse campuses. A secondary aim was to evaluate the moderating effects of heavy alcohol use on program effectiveness. Participants were 114 male college students attending a presentation of The Men’s Program on one of two campuses. Outcomes, including rape myth acceptance, bystander willingness to help, and bystander behavior, were assessed pre- and post-intervention and 1 month after completing the program. Campus-specific effects did not account for a significant amount of variance in any of these outcomes. Statistically significant reductions in rape myth acceptance (d = .32) and increases in willingness to intervene as a bystander (d = .40) were observed from pre-intervention to 1-month follow-up, although no significant changes in overall bystander behavior were observed. Across time, however, heavy drinking students were more likely to report engaging in bystander behaviors than non-heavy drinking students. Results suggest that programs can be easily implemented across different campuses and may do well to specifically emphasize effective intervention strategies relevant to social situations encountered by heavy drinking students.